Application of indole-3-butyric acid (IBA) enhances agronomic, physiological and antioxidant traits of Salvia fruticosa under saline conditions: a practical approach - Uğur Tan (PeerJ)
Background Salinity stress is a significant challenge in agriculture, particularly in regions where soil salinity is increasing due to factors such as irrigation practices and climate change. This stress adversely affects plant growth, development, and yield, posing a threat to the cultivation of economically important plants like Salvia fruticosa. This study aims to evaluate the effectiveness by proactively applying indole-3-butyric acid (IBA) to Salvia fruticosa cuttings as a practical and efficient method for mitigating the adverse effects of salinity stress. Methods The factors were arranged as three different IBA doses (0, 1, and 2 g/L) and four different salinity concentrations (0, 6, 12, and 18 dS/m) in controlled greenhouse conditions. Plant height (PH), flower spike length (FSL), fresh shoot length (FRL), root length (RL), fresh root weight (FRW), fresh shoot weight (FSW), dried root weight (DRW), dried shoot weight (DSW), root/shoot index, drog (g/plant), relative water content (RWC), relative membrane permeability (RMP), chlorophyll content (SPAD), extraction yield (%), DPPH (2,2-Diphenyl-1-picrylhydrazyl), phenol content, flavonoid content, and ABTS (2,2′-Azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) values were measured. Results The results show that as salinity doses increased, all parameters showed a decline. However, with a one-time IBA application to the plant cuttings before the rooting stage, particularly at a concentration of 2 g/L, was effective for mitigating the negative effects of salinity stress. Across all measured parameters, IBA significantly reduced the adverse impacts of salinity on Salvia fruticosa.